Ragam Gaya Visual Periklanan sebagai Media Propaganda di Era Hindia Belanda (1870-1942) - Indah Rahmawati Akbar; Galih Pranata (Tarikhuna: Journal of History and History Education, 2023)
Tracing the world of advertising which has been so varied, of course, it cannot be separated from historical developments that are very far back, which have become popular since the XVII century. This study aims to reveal the characteristics of the advertising style and branding that developed in the Dutch East Indies era, which in turn has driven Indonesian advertising rapidly until now. The method used in this study is a literature study with a historiographical approach that examines diachronically the development of advertising and branding in the 18th to early 20th centuries. The results of this study are that there are two characteristics of advertising carried out by the Dutch in the past, namely through classified ad forms and visual forms. Some advertisements are also inseparable from the development of print mass media such as newspapers and magazines which are widespread in society. Branding and advertising strategies also vary, ranging from leaflets or posters with attractive visual designs as propaganda efforts to simple columns of lines that are persuasive and propaganda.